2021
DOI: 10.3390/photonics8110505
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Enhancement of PtSe2 Photodetectors by Using Au Nanorods

Abstract: Compact and highly sensitive near-infrared photodetectors that are operable at room temperature are required for light detection and ranging and medical devices. Two-dimensional (2D) PtSe2, a transition metal dichalcogenide, is a candidate material for near-infrared light detection. However, the photoresponse properties of 2D PtSe2 are currently inferior to those of commercial materials. The localized surface plasmon resonance of Au has been widely used for photoelectric field enhancement and in photochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…This result is attributed to the short mean free path (MFP) of PtSe 2 films and increased carrier scattering at the interface with an increased number of the PtSe 2 film in vertically stacked PtSe 2 /PtSe 2 homostructures. Based on the results of a previous study, [ 36 ] the theoretical MFP of hot electrons in metals was reported as 10–60 nm. In addition, the electronic MFP of 2D bulk MoS 2 material was ≈14 nm at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This result is attributed to the short mean free path (MFP) of PtSe 2 films and increased carrier scattering at the interface with an increased number of the PtSe 2 film in vertically stacked PtSe 2 /PtSe 2 homostructures. Based on the results of a previous study, [ 36 ] the theoretical MFP of hot electrons in metals was reported as 10–60 nm. In addition, the electronic MFP of 2D bulk MoS 2 material was ≈14 nm at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the distinct temperature gradient in the longitudinal direction (∇T z ), it is sufficient for these heat carriers to affect in the out-of-plane direction since the thickness of the HR-PtSe 2 (2 nm) is shorter than the typical mean free path of carriers in 2D TMDC materials at room temperature. [43,44] This condition causes the momentum transfer of heat carriers from the HR-PtSe 2 layer to the LR-PtSe 2 layer through the interface, leading to an increase the total Seebeck coefficient compared to that of the single LR-PtSe 2 (3 nm) layer. What further supports this argument is that while these mechanisms and results are almost identical in the phonon drag effect, but the contribution of the phonon drag effect is negligible at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…These energetic electrons can then be injected into the adjacent semiconductor, such as the photoactive layer of a solar cell or the active region of a photodetector. 119,120 Once injected into the semiconductor, hot electrons can contribute to the device's performance in several ways including enhanced photocurrent, 121,122 reduced recombination losses, 121 extended spectral response, 121 and modified charge transport and recombination. 123 Hot electron transfer processes have also been investigated in plasmonic nanostructures (e.g., NCs) for solar energy harvesting.…”
Section: Perspectivesmentioning
confidence: 99%
“…Once injected into the semiconductor, hot electrons can contribute to the device's performance in several ways including enhanced photocurrent, 121,122 reduced recombination losses, 121 extended spectral response, 121 and modified charge transport and recombination. 123 Hot electron transfer processes have also been investigated in plasmonic nanostructures ( e.g.…”
Section: Perspectivesmentioning
confidence: 99%